Motivation in Information Communication and Technology-Based Science Learning in Tamil Schools (Jurnal Pendidikan IPA Indonesia, 2019)
The purpose of this study is to examine the impact of Information Communication Technology (ICT) utilisation in learning science to improve studentsâ€™ motivation. This study examined 100 students from Malaysian Tamil vernacular schools to learn ICT-based science.Research design used a mixed method approach involving quantitative and qualitative data. Students answered the Science Motivation Questionaire II (SMQ II) instrument based on the dichotomous scale that uses â€œYes or Noâ€ questions. Open-ended questions were also analysed qualitatively. The instrument was divided into five categories, namely Intrinsic Motivation, Grade Motivation, Self-efficacy Motivation, Self-determination and ICT Motivation. The findings showed that all 25 items of SMQ IIhad significantly high level of motivation. 90.2% of respondents agreed that ICT-based learning of Science stimulated their Intrinsic Motivation. Respondents admitted that factors such as Elements of ICT (46.6%), Assisted Learning (30.10%) and Stimulated Interest (23.3%) had been their attraction towards the usage of ICT in learning Science. This study also identified that respondents regarded the level of internet accessibility (34.7%) and health (25.5%) as being the main obstacles to using ICT during Science learning. Findings from this study show health issues hinder the usage of ICT in learning Science. Therefore this new element should be taken into account so as not to become a constraint for their motivation. The significance of this study is to enable Tamil vernacular school students to show interest in studying science.